Persistence and shedding of senecavirus A in naturally infected boars. (May 2022) - Sturos, Matthew J.; Murray, Deborah; Johnson, Levi; Preis, Guilherme; Corzo, Cesar A.; Rossow, Stephanie; Vannucci, Fabio A.
Senecavirus A (SVA) infection in pigs causes vesicular disease and results in a short viremia and transient shedding of the virus, mainly in oral fluids and feces. Here we describe the consistent prolonged shedding of SVA in the semen of 2 boars, and persistence of SVA within the tonsils and testes of 3 adult boars. Two SVA-infected boars that were identified on a Minnesota sow farm in 2017 shed SVA RNA in semen for >3 mo after an outbreak of vesicular disease had occurred on the farm. SVA was isolated from 1 semen sample collected 9 d after clinical disease began on the farm. The third SVA-infected boar was identified on an Indiana sow farm in 2020. All boars had SVA RNA detected in the testes and tonsils by RT-rtPCR, with lower Ct values obtained for the testes than from the tonsils. All boars had multifocal lymphocytic orchitis with segmental degeneration and atrophy of the germinal epithelium within the seminiferous tubules. One boar also had areas of seminiferous tubule collapse and interstitial fibrosis within the testes. In all boars, in situ hybridization demonstrated the presence of SVA mRNA within cells located basally in the seminiferous tubules of the testes, and within the basal surface epithelial cells, crypt epithelial cells, and subepithelial and parafollicular lymphocytes and histiocytes of the tonsil.